Thinking flexibility, rethinking boundaries: Students' educational choices in contemporary societies. (July 2018) - Tsatsaroni, Anna; Sarakinioti, Antigone
This article provides an analysis of the processes through which young people make educational choices and shape their trajectories in globalised societies of lifelong learning (LLL). Investigating the articulation of LLL discourses in national contexts and local educational sites, it draws on both Foucault and Bernstein for theoretical insights: it shows how thinking with Foucault we can better exploit the generative power of Bernstein's theory in complex fields of educational research. The article draws on a study carried out in the Greek Institutions of Vocational Education and Training (IVETs), which in response to European Union policies, offer training at post-secondary level in a range of specialties, broadening the limited choice opportunities for young people, especially of vulnerable social groups. Through semi-structured interviews with trainees, the study aimed to explore the relations between previous educational trajectories, their general understandings of LLL environments and demands, their choice to continue their learning trajectory at the IVETs, and their experience from their studies there. Tracing the movements of subjects within the temporal and spatial limits of the LLL discourses contributes in that it allows us to think of 'flexibility' as a conceptual means of identifying forms of regulation and identity formation in the new era.